2020
DOI: 10.1186/s13018-020-01674-x
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of reduction loss after arthroscopic fixation of acute acromioclavicular dislocations using a double-button device, and its effect on clinical and radiological results

Abstract: Background: The aim of this study was to investigate the effect of reduction loss of more than 3 mm on clinical and radiological results after at least 2 years of follow-up after arthroscopic fixation of acute acromioclavicular joint dislocations using a double-button device. Methods: Thirty-six patients who had acute (< 3 weeks old), type III or V acromioclavicular (AC) joint dislocations underwent arthroscopic fixation of the AC joint using a double-button device. Clinical and radiological evaluations were p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 29 publications
(47 reference statements)
1
14
0
1
Order By: Relevance
“…Our absolute values at follow-up are comparable to data in the literature, with a certain loss of reduction being known to occur with different techniques [ 5 , 36 , 37 ]. In line with our data, a recent systematic review could not detect significant differences between open and arthroscopic ACJR techniques in terms of loss of reduction and complication rate [ 37 ].…”
Section: Discussionsupporting
confidence: 86%
“…Our absolute values at follow-up are comparable to data in the literature, with a certain loss of reduction being known to occur with different techniques [ 5 , 36 , 37 ]. In line with our data, a recent systematic review could not detect significant differences between open and arthroscopic ACJR techniques in terms of loss of reduction and complication rate [ 37 ].…”
Section: Discussionsupporting
confidence: 86%
“…The most common injury mechanism in our study was traffic accidents (57.5%). However, in their studies of patients with acute AC dislocation, Çarkçı et al 8 and Olivos-Meza et al 26 stated that most injuries were sports-related (41.7% and 40.3%, respectively). We found Rockwood type 5 injuries in 24 (72.7%) patients, with a male predominance of 87.8%, which matches the findings of the previous studies.…”
Section: Discussionmentioning
confidence: 98%
“…We found Rockwood type 5 injuries in 24 (72.7%) patients, with a male predominance of 87.8%, which matches the findings of the previous studies. 8 , 26 Olivos-Meza et al 26 found that patients in whom reduction was preserved had a shorter interval to surgery than those with failed reduction ( t = 14.6; P = .0001), and the investigators advocated for early surgical intervention (before 3 weeks) to facilitate AC joint reduction. Our study disclosed a mean time elapsed before surgery of 5.3 days (range, 2-14 days), which was close to the values of Çarkçı et al 8 (6.7 days) and Olivos-Meza et al 26 (12.8 days).…”
Section: Discussionmentioning
confidence: 99%
“…Similar categorization of CCD was performed by Çarkçı et al to assess differences in clinical scores in patients with higher loss (>3 mm) in reduction compared to lesser loss (<3 mm). 15 The subacromial osteolytic zone, if present, was measured in AP view of shoulder immediately after the HP removal and again, at last, follow up to assess its continuation or resolution. The axillary view was utilized to assess the quality of reduction in the horizontal plane.…”
Section: Post-op Rehabilitation Protocol (Hp and Db Group)mentioning
confidence: 99%